Mucosal Leishmaniasis: a Rare Infection from Western Nepal - Baidya, Pooja; Mahaseth, Subash Chandra; Adhikari, Milan; Shrestha, Richa; Ghimire, Pragya Gautam (Journal of BP Koirala Institute of Health Sciences, 2023)
Leishmaniasis is a neglected tropical disease infecting world’s poorest population in over 90 countries throughout Asia, Africa, the Middle East, and Central and South Africa. An underestimated 700,000 to one million new cases occur annually. Leishmaniasis refers to a spectrum of diseases caused by a parasite, Leishmania, transmitted by bite of infected sandflies. Of the three major syndromes (cutaneous, mucosal and visceral) mucosal leishmaniasis is the least common. Despite being an endemic country for cutaneous and visceral forms, there are rare reports of mucosal form published in the literature from Nepal till date. Here we present a case of mucosal leishmaniasis presented masquerading malignancy from Dailekh District immediate proximal to Surkhet, one of the endemic districts of western Nepal.